2015
DOI: 10.3126/ijasbt.v3i3.12724
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Screening and Molecular Characterization of Thermophilic Bacterial Strains Isolated from Hotspring of Tatopani, Bhurung, Nepal

Abstract: Background and Aim: In Nepal not much of study of Thermophilic area and Thermophiles have been done. Thermophilic bacteria are less studied but are important group of microorganisms due to their ability to produce industrially important enzymes. Methods: In this study, thermophilic bacteria were isolated from hot spring of Bhurung, Nepal. Wide range of bacteria that could grow at high temperatures and tolerate extreme temperature were characterized by morphology, biochemistry and sequencing of its 16S rRNA gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(10 reference statements)
0
5
1
Order By: Relevance
“…Phylogenetic tree enables to claim that the isolates belong to five genera [ Figure 2] The detailed phylogenetic analysis of the bacterial community is first time reported from the five hot springs located in Myagdi, Nepal. Bacillus licheniformis, Bacillus subtilis, and Bacillus pumilus had been reported earlier from Bhurung hot spring [31], but these bacteria were not found in the present study. Anoxybacillus sp., Brevibacillus sp., and Aeribacillus sp.…”
Section: S Rrna Gene Sequence and Phylogenetic Analysiscontrasting
confidence: 54%
See 1 more Smart Citation
“…Phylogenetic tree enables to claim that the isolates belong to five genera [ Figure 2] The detailed phylogenetic analysis of the bacterial community is first time reported from the five hot springs located in Myagdi, Nepal. Bacillus licheniformis, Bacillus subtilis, and Bacillus pumilus had been reported earlier from Bhurung hot spring [31], but these bacteria were not found in the present study. Anoxybacillus sp., Brevibacillus sp., and Aeribacillus sp.…”
Section: S Rrna Gene Sequence and Phylogenetic Analysiscontrasting
confidence: 54%
“…Till date, B. licheniformis, B. subtilis, and B. pumilus have been reported from Bhurung hot spring of Myagdi district, Nepal [31]. This is the first study on the microbial diversity of thermophiles in five different hot springs of Myagdi district.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies within the past two decades have reported on the under exploration of about 99% of microorganisms in this group. However, only a few have been cultivated in laboratories, causing optimization failures encountered in biotechnology and industrial application (Adhikari et al 2015). Generally, microorganisms have been identified as the best source of enzymes, due to their ability to culture in large quantities, and within a relatively short time, alongside the higher stability, compared to plant and animal sources (Acharya and Chaudhary 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme activity assay included α-amylase (Khalil, 2011), cellulase using cellulose powder and carboxymethyl cellulose (CMC) as substrates (Teather and Wood, 1982), caseinase (Adhikari et al, 2015), pectinases (Huang et al, 2012) and xylanases (Gessesse and Gashe, 1997). Incubation was done at 55°C for 48 h. The diameter of the clear zones was measured using a ruler.…”
Section: Enzyme Activities Of the Selected Isolatesmentioning
confidence: 99%
“…Thermotolerant bacteria have attracted industrial and biotechnological attention as their enzymes are well suited for harsh industrial processes (Abdel-Rahman et al, 2016;Archna et al, 2015;Verma et al, 2015). Proteases obtained from thermophilic or thermotolerant (Adhikari et al, 2015;Bozoglu et al, 2015;Lele and Deshmukh, 2016;Panda et al, 2013;Remigio et al, 2012;Verma et al, 2014) bacteria, for example, have found applications such as hide dehairing in the leather industry and stain removal in laundry detergents (Chandrashekhar and Narayan, 2015;Dudhgara et al, 2015;Jaouadi et al, 2013). Cellulases have showed great potential in the production of bioethanol and other speciality chemicals from renewable agricultural residues (Hardiman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%